Moving at the Speed of Business: A Possible Path to First Nation Prosperity Starts with Efficiency - Le Dressay, Andre; Reeves, Jason; Lavallee, Normand (Journal of Aboriginal Economic Development, 2024)
First Nation economic self-determination strategies are constrained by high investment facilitation transaction costs and high jurisdictional implementation switching costs. This paper summarizes a First Nation-led strategy to overcome these constraints. This strategy, which began 55 years ago, uses federal legislation such as the First Nations Fiscal Management Act (FMA) and the Framework Agreement on First Nations Land Management (FA). It is supported by First Nation institutions such as the First Nations Tax Commission, First Nations Financial Management Board, First Nations Land Management Resource Centre, First Nations Finance Authority, and the newly established First Nations Infrastructure Institute. Preliminary observations suggest the FMA-FA strategy has successfully reduced transaction and switching costs on First Nation lands and could accelerate economic self-determination for interested First Nations.